Sub-District Leadership with Public Awareness in Paying Land and Building Tax in Gilireng Sub-District, Wajo Regency - Herlina Sakawati; Besse Heriayu; Novayanti Sopia Rukmana (Universitas Negeri Makassar, 2024)
This study aims to determine the relationship between sub-district leadership and community awareness in paying land and building taxes in Gilireng District, Wajo Regency. This study used quantitative methods. To achieve this goal, data collection techniques in the form of observation, questionnaires and documentation are used. The samples used were 95 samples. The data obtained was processed using data analysis and using the SPSS 25 application consisting of normality tests, linearity tests, validity tests, reliability tests and regression tests. The results showed that the Subdistrict Leadership variable (X) consisted of indicators of leadership style, leadership traits and contingency approach. Meanwhile, in variable Y which consists of indicators of the social structure of the community, the government's efforts to socialize taxes and procedures that make it easier to pay taxes have a positive and significant influence. This is evidenced by the results of a simple linear regression analysis with a correlation coefficient of 70%.